Immediate breast reconstruction in high-risk cases using an anatomically shaped permanent expandable implant. Issue 3 (March 2019) - Kedar, Daniel; Inbal, Amir; Arad, Ehud; Gur, Eyal; Barnea, Yoav
Summary: Background: Anatomically shaped permanent expandable implants are dual-chambered devices, which allow their postoperative expansion for the adjustment of volume. Their use is optional when 1-stage immediate breast reconstruction (IBR) direct to permanent implant is not feasible. The aim of this study is to present one center's long-term experience with the anatomical Becker expandable implant in a large series of patients who underwent either IBR or a salvage procedure for IBR with the device. Methods: The records of 141 patients (a total of 161 breasts) who underwent IBR with the Becker implant were retrospectively reviewed. Patient demographics and surgical outcomes were analyzed. Indications for this procedure included reduced skin envelopes, compromised skin flaps, salvage procedures, and single-stage procedures in patients with major comorbidities. Results: One hundred twenty-three devices (76%) involved IBR and 38 devices (24%) were salvage cases after direct-to-implant IBR. The device was used in a previously radiated breast in 36 cases (22%). Long-term follow-up demonstrated that 99 devices (61.5%) had been exchanged or removed and that only 62 devices (38.5%) remained as permanent implants. Removal of the device was associated with prior breast radiation and advanced age. Conclusions: The use of the Becker device in high-risk IBR cases had a low retention rate as a permanent implant. Favorable indications for the use of this device in IBR cases include contralateral breast augmentation and patients with major comorbidities, which demonstrated a higher retention rate. Other indications for high-risk IBR cases could probably benefit using a 2-stage tissue-expander and implant technique.